A Descriptive-Correlational Study on Learning Ability and Readiness to Practice Among Nursing Graduates in a Private Chinese Institution - Li, Liwei; F. Lazaro, Leslie (Journal of Neonatal Surgery, 2025)
This study investigates the relationship between individual learning ability and readiness to practice among nursing graduates from a private health sciences institution in Hebei Province, China. Framed by Attribution Theory, which explores how individuals attribute causes to their successes and failures, the study examines how learning habits and learning aids correlate with readiness to practice across physical, emotional, and psychosocial domains. A descriptive-correlational research design was employed, and data were collected through a validated survey instrument administered to 377 third-year nursing students (67% female, aged 20–21; 56% from middle-income households). Spearman's rho correlation analysis revealed statistically significant relationships between learning ability and readiness to practice (r = 0.697, p < .001), with socioeconomic status (p = 0.024) and clinical performance (p = 0.015) emerging as significant influencing factors. Targeted interventions such as structured self-directed learning (SDL) training, technology lending programs, and stress-management modules are recommended to bridge gaps in clinical preparedness. These findings highlight the importance of fostering learning habits, providing equitable access to learning aids, and implementing evidence-based reforms to enhance nursing students' readiness for licensure and clinical practice.